Managerpolitiek. Waarom historici oog voor management moeten hebben - Kroeze, Ronald; Keulen, Sjoerd; Keulen, Sjoerd (BMGN - Low Countries Historical Review, 2012)
Manager Politics: Why Historians should be Aware of ManagementThis article pleads for the incorporation of methods of (public) management and public administration sciences in the writing of political (cultural) history. These help historians to become more sensitive to the language and influence of managers and management in politics, enabling them to understand the era of manager politics that established itself from the 1980s onwards. The insights and gains of the new approach are illustrated by the case of Dutch politics during the cabinets of Prime Ministers Lubbers (1982-1994) and Kok (1994 2002) that show how politics became dominated by management. This led to important changes in the complement of staffing and behaviour of political parties, the cabinet and the public administration. How manager politics altered power relations is illustrated by the easy adoption of new routines and policies based on management (gurus). This article is part of the forum 'Manager Politics'.